2021
DOI: 10.48550/arxiv.2109.08408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finite-Size scaling analysis of many-body localization transition in quasi-periodic spin chains

Adith Sai Aramthottil,
Titas Chanda,
Piotr Sierant
et al.

Abstract: We analyze the finite-size scaling of the average gap-ratio and the entanglement entropy across the many-body localization (MBL) transition in one dimensional Heisenberg spin-chain with quasiperiodic (QP) potential. By using the recently introduced cost-function approach, we compare different scenarios for the transition using exact diagonalization of systems up to 22 lattice sites. Our findings suggest that the MBL transition in the QP Heisenberg chain belongs to the class of Berezinskii-Kosterlitz-Thouless (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 95 publications
1
4
0
Order By: Relevance
“…[39] and found broadly consistent results, however it would be interesting to revisit this assumption in light of the recent results of Ref. [43]. We further suggest a connection to the work of Ref.…”
Section: Evidence For a Delocalization Phase Transitionsupporting
confidence: 74%
See 4 more Smart Citations
“…[39] and found broadly consistent results, however it would be interesting to revisit this assumption in light of the recent results of Ref. [43]. We further suggest a connection to the work of Ref.…”
Section: Evidence For a Delocalization Phase Transitionsupporting
confidence: 74%
“…In the late stages of completion of this work, we became aware of a recent preprint (Ref. [43]) which conducted a careful finite-size scaling analysis of the MBL transition in a quasiperiodic system and concluded that, for system sizes accessible to ED, the best data collapse was achieved with the assumption of a Berezinskii-Kosterlitz-Thouless (BKT) scaling form, as also seen in recent numerical studies on random systems. This result is a surprise in a quasiperiodic system, as the rare ergodic seed regions which lead to avalanaches and a BKT-like transition are not currently known to exist in deterministic potentials, and is in contrast with Refs.…”
Section: Evidence For a Delocalization Phase Transitionmentioning
confidence: 81%
See 3 more Smart Citations